Corporate Energy Transformation As A Development Direction In The Context of Eco-Innovation - Ilona DZIEDZIC-JAGOCKA; Aleksandra KUMOR-SULERZ (Communications of International Proceedings, 2023)
This article presents a proposal for change in the context of eco-innovation for an enterprise in which energy is the dominant source of negative environmental impact. An assessment of the enterprise was carried out using an original method of diagnosing the state of enterprise innovation, which uses the LCA method to examine the eco-innovation of an enterprise. The study showed that electricity consumption in production processes is the primary source of a company's negative environmental impact. Therefore, in order to improve energy efficiency, the enterprise should take eco-innovative measures in the processes used. Therefore, the proposed energy transformation solution for the enterprise consists of a hybrid renewable energy installation with an energy storage facility based on green hydrogen technology. This solution responds to the Green Deal strategies to achieve climate neutrality.
Keywords: Innovation enterprise; Life Cyce Assessment (LCA); energy transition.